2021
DOI: 10.1001/jamapediatrics.2020.3557
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of a Home-Visiting Intervention to Reduce Early Childhood Obesity Among Native American Children

Abstract: IMPORTANCEEarly childhood obesity disproportionately affects Native American communities. Home visiting is a promising strategy for promoting optimal infant growth in this population.OBJECTIVE To assess the impact of a brief home-visiting approach, Family Spirit Nurture (FSN), on sugar-sweetened beverage (SSB) consumption, responsive parenting and infant feeding practices, and optimal growth through 12 months post partum. DESIGN, SETTING, AND PARTICIPANTSThis study was a 1:1 randomized clinical trial comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…In 1956, the average Navajo BMI was 23.5 for men and for 22.9 women, when their saturated fat intake (mainly mutton and lard-fried bread) was as high or higher than White Americans ( 102 ). In 2020, average BMI for Navajo women was 31.2 ( 103 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 1956, the average Navajo BMI was 23.5 for men and for 22.9 women, when their saturated fat intake (mainly mutton and lard-fried bread) was as high or higher than White Americans ( 102 ). In 2020, average BMI for Navajo women was 31.2 ( 103 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our experience in the field when collecting dietary recalls at the 24-month follow-up posed a heavy burden on participants and meant that applying a more intensive dietary assessment tool at the 36-month follow-up was not possible. A longer period may need to pass among children in the delayed 21 Although the intervention attempted to improve early feeding practices, contrary to expectations, a higher proportion of infants in the intervention group were introduced to…”
Section: Discussionmentioning
confidence: 96%
“…The dietary intervention was designed in conjunction with Navajo communities and was delivered from 3 to 6 months by Navajo paraprofessionals. 21 Although the intervention attempted to improve early feeding practices, contrary to expectations, a higher proportion of infants in the intervention group were introduced to…”
Section: Discussionmentioning
confidence: 99%
“…Evidence‐based home visiting programs are recognized for their sustainable and positive impact as an early intervention strategy within community settings but face shared challenges in implementation. During research trials, home visiting programs have demonstrated significant impact in identifying and addressing child behavioral problems, child obesity, family nutrition, maternal depression, substance misuse, and intimate partner violence (Barlow et al., 2015; Dauber et al., 2017; Haroz et al., 2019; Rosenstock et al., 2021; Tandon et al., 2020). Family Spirit (FS), an evidence‐based, federally endorsed, culturally congruent home‐visiting intervention that is delivered by paraprofessionals, is a model program that holds the collective aims of improving parental competencies and children's and parent's social, emotional, and behavioral outcomes (Mullany et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The FS model demonstrates a strong foundation in terms of format and lesson delivery to address community‐specific needs. For example, the FS Nurture intervention study implemented the same format and delivery of lessons used in FS to deliver nutrition‐focused lessons to address childhood obesity and demonstrated post‐intervention protective effects against sugar‐sweetened beverages consumption, responsive feeding, and infant body mass index scores in a tribal community setting (Rosenstock et al., 2021). Secondary analysis of the FS intervention study (Barlow et al., 2015) revealed that children born to mothers with a history of alcohol, marijuana, or illicit substances demonstrated greater improvements in emotional and behavioral outcomes after receiving FS, which includes a substance use during pregnancy lesson, in comparison to their counterparts that did not receive the intervention (Haroz et al., 2019).…”
Section: Introductionmentioning
confidence: 99%